Case of Dividend Payout Ratio (DPR): Evidence on Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange - S. Surtikanti; J. Octavia; I. Martina (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aims to determine the effect of Net Profit and Debt Equty Ratio on the Dividend Payout Ratio. This research was conducted on Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange.The research method used is descriptive analysis and verification analysis method with a population of 185 financial reports from 37 companies with sample selection using the Purposive Sampling method and the research sample obtained is 50 financial statements from 10 companies. The data analysis method used is multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing using ttest. The results showed that the Dividend Payout Ratio was significantly affected by Net Profit with a positive relationship, and significantly influenced by the Debt to Equity Ratio with a negative relationship. Partially, the Dividend Payout Ratio is more dominantly influenced by Net Profit compared to the Debt to Equity Ratio, it means that the greater the net profit obtained, the greater the dividend paid. The results of this research are expected to provide input for investors in analyzing the Dividend Payout Ratio.